The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/09544089211021274
|View full text |Cite
|
Sign up to set email alerts
|

CFD simulation of HC-290 leakage from a split type room air conditioner

Abstract: HC-290 is one of the alternatives to HCFC22 in room air-conditioners. With the phase-down schedules in Kigali Amendment, it is imperative to use HC-290. However, there are concerns about its flammability in the event of a leak from the AC indoor unit (IDU). IEC 60335-2-40 has been revised to extend the capacity ranges for A2L refrigerants and is being further revised with a focus on A2 and A3 refrigerants. In real-life situations, furniture and occupants are present inside the room and these may positively or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 18 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Cai et al [21] studied the diffusion process and concentration distribution of R290 after it leaked from a wall-mounted air conditioner into three rooms with different sizes; the results found that the larger space was more conducive to the dilution and uniform distribution of the leaked refrigerant. Prakash et al [22] analyzed the effects of leakage rate, indoor unit installation height, whether an indoor fan was on or off, and the type of furniture placed in the external space on the concentration distribution of leaked R290 in a wall-mounted air conditioner. Hu et al [23] studied the influence of the airflow rate and angle of the indoor unit on the diffusion process of R290 in a wall-mounted air conditioner, and the results showed that the airflow rate could dominate the diffusion of the leaked refrigerant, and the airflow angle only affected the dispersion when the velocity was small, and upward blowing was more conducive to uniform distribution of the refrigerant.…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al [21] studied the diffusion process and concentration distribution of R290 after it leaked from a wall-mounted air conditioner into three rooms with different sizes; the results found that the larger space was more conducive to the dilution and uniform distribution of the leaked refrigerant. Prakash et al [22] analyzed the effects of leakage rate, indoor unit installation height, whether an indoor fan was on or off, and the type of furniture placed in the external space on the concentration distribution of leaked R290 in a wall-mounted air conditioner. Hu et al [23] studied the influence of the airflow rate and angle of the indoor unit on the diffusion process of R290 in a wall-mounted air conditioner, and the results showed that the airflow rate could dominate the diffusion of the leaked refrigerant, and the airflow angle only affected the dispersion when the velocity was small, and upward blowing was more conducive to uniform distribution of the refrigerant.…”
Section: Introductionmentioning
confidence: 99%